2022
DOI: 10.7554/elife.70684
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular electron transfer increases fermentation in lactic acid bacteria via a hybrid metabolism

Abstract: Energy conservation in microorganisms is classically categorized into respiration and fermentation; however, recent work shows some species can use mixed or alternative bioenergetic strategies. We explored the use of extracellular electron transfer for energy conservation in diverse lactic acid bacteria (LAB), microorganisms that mainly rely on fermentative metabolism and are important in food fermentations. The LAB Lactiplantibacillus plantarum uses extracellular electron transfer to increase its NAD+/NADH ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
69
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(88 citation statements)
references
References 119 publications
(131 reference statements)
8
69
0
Order By: Relevance
“…Dynamic binding between eDNA and electron shuttles in oxidized or reduced states accelerates electron exchange. During food fermentation, some LAB, including Lactiplantibacillus plantarum, were found to use a hybrid strategy to conserve energy, in that the LAB used extracellular electron transfer to increase the NAD+/NADH ratio and then generated more ATP through substrate-level phosphorylation (Tejedor-Sanz et al, 2022). This suggested a regulatory approach using extracellular electron transfer to modulate the microbial biomass, metabolic flux, product yield, and flavor profiles of fermented foods.…”
Section: Cross-respiration and Extracellular Electron Transfermentioning
confidence: 99%
“…Dynamic binding between eDNA and electron shuttles in oxidized or reduced states accelerates electron exchange. During food fermentation, some LAB, including Lactiplantibacillus plantarum, were found to use a hybrid strategy to conserve energy, in that the LAB used extracellular electron transfer to increase the NAD+/NADH ratio and then generated more ATP through substrate-level phosphorylation (Tejedor-Sanz et al, 2022). This suggested a regulatory approach using extracellular electron transfer to modulate the microbial biomass, metabolic flux, product yield, and flavor profiles of fermented foods.…”
Section: Cross-respiration and Extracellular Electron Transfermentioning
confidence: 99%
“…Lactic acid bacteria represent a family of non-pathogenic, non-sporulating, microaerophilic, Gram-positive bacteria that produce lactic acid as the major end resultant during carbohydrate fermentation and have been employed in food supplements, medicines, and cosmetics for ages to promote modern human civilization [1,2]. LAB are generally recognized as safe (GRAS) and due to this status, these food-grade Gram-positive bacteria have been used as starter cultures for food fermentation and as cell factories for the production of various macromolecules, enzymes, and relevant metabolites in the food, pharmaceutical, and dietary supplement industries [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…This allowed us and others to identify other Gram-positive microbes capable of EET, including Enterococcus faecalis and Lactiplantibacillus plantarum. 5,[7][8][9] At present, however, it is not understood how exclusively fermentative microbes, such as L. plantarum and E. faecalis, can utilize and maintain an EET pathway, especially when a traditional respiratory system is not maintained. Elucidating this phenomenon and its influence on organismal physiology is of great importance due to the prevalence of these Gram-positive bacteria in agriculture, bioremediation, food production, gut health, and opportunistic human infections.…”
mentioning
confidence: 99%
“…We recently showed that the genus Lactiplantibacillus has a highly conserved FLEET locus and many of its members exhibit EET activity. 9 The FLEET locus encodes a type-II NADH dehydrogenase (Ndh2), flavin transport proteins (FmnA/B and ATPase1/2), membrane demethylmenaquinone (DMK) synthesis proteins (DmkA and EetB/DmkB), and electron transfer proteins (PplA and EetA). [7][8][9] An exogenous menaquinone (MK) precursor, 1,4-dihydroxy-2naphthoate (DHNA), was added to allow the microbe to synthesize MK or DMK.…”
mentioning
confidence: 99%
See 1 more Smart Citation